HUBUNGAN LAMANYA SAKIT, USIA DENGAN KEPATUHAN MINUM OBAT PADA PASIEN SYSTEMIC LUPUS ERYTHEMATOSUS DI KOMUNITAS LAMPUNG TAHUN 2019 - Okvien Puspita Sari; Resati Nando Panonsih; Ratna Purwaningrum; Firhat Esfandiari (HUMAN CARE JOURNAL, 2020)
Systemic Lupus Erythematosus (SLE) is a systemic disease with the characteristics of the antinuclear antibody (ANA) that attacks the vascular system and connective tissue. SLE is more common in women of childbearing age with a vulnerable age 15 to 45 years. To improve the quality of life, a Odapus (people with Lupus) should consume a variety of drugs all his life To determine the correlation between of the length of illness, age of the patient taking medication compliance Systemic Lupus Erythematosus in Comunity Lampung 2019. This type of research is research analytic method with cross sectional approach. Samples of this research that people with lupus in Lampung as many as 26 people. Data obtained through questionnaires filled medication adherence, age and informed consent questionnaire. Data analysis techniques to test the hypothesis that statistic Pearson. There research showed a correlation between age and medication adherence which from a statistical test Pearson gained significance level (p-value) amounted to (0.134), which means greater than the value of alpha (0.05) and no significant correlation between the duration of illness and whereby adherence of the statistical test Pearson gained significance level (p-value) amounted to (0.060), which means greater than the value of alpha (0.05).